DAMPAK KONVERGENSI INTERNATIONAL FINANCIAL REPORTING STANDARDS TERHADAP NILAI RELEVAN INFORMASI AKUNTANSI - Suprihatin, Siti; Tresnaningsih, Elok (Jurnal Akuntansi dan Keuangan Indonesia, 2013)
This study investigates whether the convergence of the International Financial Reporting Standards (IFRS) increase the value relevance of accounting information of firms listed on Indonesia Stock Exchange. This study covers periods pre-IFRS convergence and post-IFRS convergence during 2006-2011. We tested the value relevance of book value of equity and earnings in pre- and post- IFRS convergence. We find that on the beginning stage of IFRS convergence, earnings become more value-relevant whereas the book value of equity does not. Meanwhile, on the advance stage of IFRS convergence, we find book value of equity and earnings are more value-relevant. Besides that, this study also provides sensitivity analysis which revealed empirical result from a modification of model.